Enhancing Autonomy in Language Education. A Case-Based Approach to Teacher and Learner Development - Vieira, Flávia (Studies in Second and Foreign Language Education [SSFLE], 2015)
The enhancement of autonomy in language education relies heavily on teachers` empowerment and agency as critical intellectuals and reflective practitioners. However, most teacher education programmes are still based on instrumental views of teacher development that undervalue professional experience and expertise. The authors set the ground for alternative practices by proposing and illustrating a case-based approach to language teacher education that values experiential professional learning and expands competences to promote autonomy in school.